Heat‐shock protein 70—a hub gene—underwent adaptive evolution involved in whitefly‐wild tomato interaction. Issue 11 (21st July 2022) - Tian, Jiahui; Dewer, Youssef; Qu, Cheng; Li, Fengqi; Luo, Chen
Abstract: BACKGROUND: The whitefly Bemisia tabaci causes severe damage to cultivated tomato plants, but actively avoids the wild tomato Solanum habrochaites . Moreover, the mortality of whitefly increases significantly after feeding with the wild tomato. However, additional experiments are warranted to more carefully elucidate the specific molecular elements underlying the interaction between whitefly and wild tomato. RESULTS: Our results showed that S. habrochaites significantly increases the mortality of whitefly adults and decreases both their fertility and fecundity. In addition, the expression of stress‐response genes in whitefly after exposure to S. habrochaites was analyzed using RNA sequencing. Weighted gene co‐expression network analysis was conducted to identify the hub genes to determine their potential associations with the mortality of whitefly. These results suggested that the expression of heat‐shock protein (HSP), multicopper oxidase, and 2‐Oxo‐4‐hydroxy‐4‐carboxy‐5‐ureidoimidazoline (OHCU) decarboxylase genes were induced in whitefly. To validate the gene associations with whitefly mortality, a high‐throughput in vivo model system and RNAi‐based gene silencing were used. The results revealed that the RNAi‐mediated depletion of the HSP gene, which belongs to the HSP70 subfamily, increased the mortality of whitefly. Furthermore, the selection pressure analysis showed that a total of five amino acid sites of positive selection were identified, three of which were located in the nucleotide‐binding domain and the other two in the substrate‐binding domain. CONCLUSIONS: This is the first report on the potential implication of HSPs in whitefly–wild plant interactions. This study could more precisely identify the molecular mechanisms of whitefly in response to wild tomatoes. © 2022 Society of Chemical Industry. Abstract : Solanum habrochaites can significantly increase the mortality of Bemisia tabaci adults and reduce both fecundity and egg hatchability. Weighted gene co‐expression network analysis (WGCNA) was conducted to identify the hub genes to determine their potential associations with the mortality of whitefly. Through RNAi and in vivo functional validation, we found that the heat‐shock protein (BTA011604) ‐interference, which belongs to the heat shock protein 70 subfamily, increased the mortality of whitefly. Futher, the selection pressure analysis showed that this gene was under positive selection pressure. A total of five amino acid sites of positive selection were identified. Three of them were located in the IIA of the nucleotide‐binding domain and the other two were located in the α‐helical subdomain of the substrate‐binding domain. These results indicate that HSP70 is involved in the stress response of whitefly to S. habrochaites . This is the first report on the potential implication of HSPs in whitefly–wild plant interactions.